Synthesis of 1,4-imino-L-lyxitols modified at C-5 and their evaluation as inhibitors of GH38 α-mannosidases - Bella, Maroš; Šesták, Sergej; Moncoľ, Ján; Koóš, Miroslav; Poláková, Monika (Beilstein Journal of Organic Chemistry, 2018)
A synthetic approach to 1,4-imino-L-lyxitols with various modifications at the C-5 position is reported. These imino-L-lyxitol cores were used for the preparation of a series of N-(4-halobenzyl)polyhydroxypyrrolidines. An impact of the C-5 modification on the inhibition and selectivity against GH38 α-mannosidases from Drosophila melanogaster, the Golgi (GMIIb) and lysosomal (LManII) mannosidases and commercial jack bean α-mannosidase from Canavalia ensiformis was evaluated. The modification at C-5 affected their inhibitory activity against the target GMIIb enzyme. In contrast, no inhibition effect of the pyrrolidines against LManII was observed. The modification of the imino-L-lyxitol core is therefore a suitable motif for the design of inhibitors with desired selectivity against the target GMIIb enzyme.
Keywords: azasugars; hydrolases; inhibitors; pyrrolidines; synthesis